Challenges of Implementing EMKM SAK in the Digitalization of MSMEs: A Qualitative Study of Business Actors' Perceptions in the 5.0 Era - Riska Pradisa; Amiruddin Islami MQ. Baba (Baca Dulu Publisher, 2026)
This study examines the application of the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) to several MSMEs in Indonesia. The method used is descriptive qualitative, with analysis of financial statements based on SAK EMKM. The results show that the implementation of SAK EMKM helps MSMEs improve transparency and understanding of their financial condition. However, obstacles remain, such as limited accounting knowledge and a lack of technical training for business actors.